2016
DOI: 10.1093/ndt/gfw008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype on the severity and volume progression of polycystic liver disease in autosomal dominant polycystic kidney disease

Abstract: In contrast to the renal phenotype, the ADPKD genotype was not associated with the severity or growth rate of PLD in ADKPD patients. This finding, along with gender influence, indicates that modifiers beyond the disease gene significantly influence the liver phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
71
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 33 publications
7
71
2
1
Order By: Relevance
“…In our population, the proportion of patients who are symptomatic (Qian Grade 4) is equal between ADPKD and ADPLD, even as the distribution between mild, moderate and severe disease which supports the homogeneous composition of this cohort. Compared with other ADPKD cohorts in which the appearance of PLD is no inclusion criteria, the proportion of females in our ADPKD population is higher . This corresponds with the results of our study and previous literature as females are more at risk to develop severe hepatomegaly and therefore are more often tertiary referred because of symptomatic PLD compared with males.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our population, the proportion of patients who are symptomatic (Qian Grade 4) is equal between ADPKD and ADPLD, even as the distribution between mild, moderate and severe disease which supports the homogeneous composition of this cohort. Compared with other ADPKD cohorts in which the appearance of PLD is no inclusion criteria, the proportion of females in our ADPKD population is higher . This corresponds with the results of our study and previous literature as females are more at risk to develop severe hepatomegaly and therefore are more often tertiary referred because of symptomatic PLD compared with males.…”
Section: Discussionsupporting
confidence: 87%
“…An important finding is that in female patients, liver volume is 6.9% smaller per decade of age. This contrasts with a recent study that suggested that hTLV increased with 10.0% per decade in female APDKD patient . These conflicting conclusions can be attributed to differences in disease populations.…”
Section: Discussioncontrasting
confidence: 83%
“…Recent studies have shown a substantial reduction in the rate of growth or even a reduction in LV in female patients after menopause. 13,14 Therefore, young premenopausal women and men with severe PLD might have a higher risk for sustained and faster enlargement of the liver after PHCF. Perioperative complications associated with PHCF were common but manageable in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…11 In contrast, the severity of polycystic liver disease seems similar in patients with PKD1 and PKD2 mutations. 17 …”
mentioning
confidence: 99%